Noninvasive early detection of focal cerebral ischemia. - Ji-Wu Zhang (IEEE Engineering in medicine and biology magazine)
Describes analyzing somatosensory evoked potentials for detecting cerebral injury in its earlier phases. Cerebral vascular diseases (CVDs) are significant factors in causing morbidity and mortality. Early diagnosis is the key to rapid recovery and improve prognosis. Most CVDs are associated with brain ischemia/hypoxia, making ischemic cerebral vascular disease a major concern. A noninvasive technique for early detection of focal brain ischemic injury is a major need. Here the authors discuss a technique to help meet this need. They present a model of SD rat focal cerebral ischemia. A new high-resolution time-frequency analysis method-the discrete Cabor spectrogram-is introduced to analyze somatosensory evoked potential signals for early noninvasive detection of brain focal ischemic injury. The time-varying spectrum of the SEP is displayed as a contour map on the two-dimensional time-frequency plane. The difference between ischemic and normal regions can be clearly seen on this map, which may be useful for diagnostic purposes.